Electroacupuncture May Inhibit Oxidative Stress of Premature Ovarian Failure Mice by Regulating Intestinal Microbiota. (30th August 2022) - Geng, Zixiang; Nie, Xiaoli; Ling, Lele; Li, Bingrong; Liu, Peng; Yuan, Long; Zhang, Kaiyong; Liu, Te; Zhang, Bimeng
Abstract : Premature ovarian failure (POF) is the leading cause of female infertility, and there is no optimal treatment or medication available currently. For POF, electroacupuncture (EA) has been considered a promising therapeutic approach, but the mechanism for this is not clear. In this study, we explored the effects of EA (CV4, ST36, and SP6) on oxidative stress and intestinal microbiota of high-fat and high-sugar- (HFHS-) induced POF mice. The development of mice follicles was observed by hematoxylin and eosin (HE) staining. The serum levels of estrone (E1), estrogen (E2), estriol (E3), and 21-deoxycortisol (21D) were measured by the HPLC-MS/MS method. The concentrations of Fe 2+, superoxide dismutase (SOD), hydroxyl radical (·OH), glutathione (GSH), superoxide anion, and malondialdehyde (MDA) were measured by spectrophotometry. The 16S-rDNA sequencing was used to measure many parameters related to the host gut bacteriome and mycobiome composition, relative abundance, and diversity. mRNA expression levels of ferroptosis-related genes were determined by RT-qPCR. After 4 weeks of EA intervention in POF mice, mature follicles were increased and the levels of the sex hormone were improved. SOD activities, antisuperoxide activities, and GSH increased while MDA, · OH, and Fe 2+ decreased. In addition, EA also altered the intestinal microbiota. These results reveal that EA can effectively inhibit ovarian oxidative stress and the accumulation of Fe 2+ in POF mice. It may be that the alteration in the intestinal microbiota is one of the potential mechanisms of EA treatment. These findings suggest that EA has clinical potential as a safe treatment for POF.